The Relationship between CRM, Knowledge Management, Organizational Commitment, Customer Profitability, and Customer Loyalty: The Mediating Role of Customer Satisfaction and the Moderating Role of Brand Image (A Study on Cement Retailers in Solo Raya) - Ramadhan, Fahrizal; Wahyudi, Lilik (Universitas Muhammadiyah Pontianak, 2025)
This study analyzes the relationships between organizational commitment (OC) and knowledge management (KM) on CRM, as well as its impact on customer profitability (CP) and customer loyalty (CL) through customer satisfaction (CS), and also the role of brand image (BI) as a moderating variable. Using a quantitative approach via SmartPLS4, data were collected from 175 cement retailer sector customers in the Solo Raya region through structured online and offline surveys. Furthermore, CRM significantly enhances customer satisfaction, customer profitability, and customer loyalty. CRM also has an indirect significant effect on customer profitability and customer loyalty through customer satisfaction as a mediator. Additionally, customer profitability contributes positively to customer loyalty. The moderating effect of brand image is proven to strengthen the relationship between CRM and customer satisfaction, customer profitability, and customer loyalty. Overall, this study suggests that importance of CRM strategies supported by strengthened knowledge management and organization commitment for customer needs to gain a competitive advantage and achieve the long-term sustainability in the industry.